PENYELESAIAN KONFLIK TANAH ANTARA DESA SUNGAI AKAR DENGAN TAMAN NASIONAL BUKIT TIGA PULUH OLEH PEMERINTAH KABUPATEN INDRAGIRI HULU TAHUN 2017-2020 - Elin Safitri; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The existence of TNBT is considered detrimental by the surrounding population because with the existence of TNBT they cannot reclaim their ancestral land, whether it is still in the form of forests, gardens and also the tombs of their ancestors who are included in the TNBT area. The problems that occur include land conflicts between Sungai Akar Village, Batang Gansal District and Bukit Tiga Puluh National Park. The community claims that 3,994 ha of land is included in the TNBT area and there is a misunderstanding about the boundaries. This study aims to describe the causes of land conflicts between Sungai Akar Village and TNBT and to describe the process of resolving land conflicts between Sungai Akar Village and TNBT by the Indragiri Hulu Regency Government. The research approach used is a qualitative approach and the type of descriptive research. The location of this research was in Sungai Akar Village and Bukit Tiga Puluh National Park Hall, and data collection techniques were carried out by interview and documentation. The cause of the conflict between Sungai Akar Village and TNBT is caused by human interests or needs, and transformation. The result of this research is that the settlement of the land conflict between Sungai Akar Village and TNBT organized by the Inhu Regency Government has not been able to be resolved with what the Sungai Akar Village party wants because the TNBT has not been able to respond or issue the customary land because the decision is based on the Center or the Ministry of Forestry. Keywords: Land Conflict, Conflict Resolution